Laboratory preparation of monochloramine for environmental research: a comparison of four commonly used protocols - Sakcham, Bairoliya (2022)
Monochloramine (MCA) is often used as a secondary disinfectant in drinking water distribution systems (DWDS) for controlling the regrowth of microorganisms. Laboratory experiments to study the efficacy of MCA and formation of disinfection byproducts in DWDS all require the preparation of MCA. Different protocols for the preparation of MCA have been used in the literature. In this study, we compared four published protocols that are frequently used to prepare MCA in the environmental research community. Our results showed that the choice of protocol could result in substantial differences in decay kinetics and disinfection efficacy of the prepared MCA. The discrepancies highlight an immediate need for the standardization of MCA preparation protocols for laboratory-scale drinking water research.